Immigration, citizenship, and the size of government - Francesc Ortega (Institute for the Study of Labor (IZA), 2009)
This paper analyzes the political sustainability of the welfare state in an environment where immigration is the main demographic force and where governments are able to influence the size and skill composition of immigration flows. Specifically, I present a dynamic political-economy model where both income redistribution and immigration policy are chosen by majority vote. Voters take into account their children's prospects of economic mobility and the future political consequences of today's policies. Over time, the skill distribution evolves due to intergenerational skill upgrading and immigration. I consider three immigration and citizenship regimes. In the first, immigrants stay permanently in the country and citizenship is obtained by birthplace (jus soli). In the second regime immigration is also permanent but citizenship is passed only by bloodline (jus sanguinis). In the third regime immigrants are only admitted temporarily and cannot vote. Our main finding is that under permanent migration and jus soli there exist equilibria where income redistribution is sustained indefinitely, despite constant skill upgrading in the population. However, this is not the case in the other two regimes. The crucial insight is that unskilled voters trade off the lower wages from larger unskilled immigration with the increased political support for redistributive transfers provided by the children of the current immigrants. In contrast, in the regimes where immigrants and their children do not gain the right to vote, unskilled voters oppose any unskilled immigration and political support for income transfers vanishes. We argue that these mechanisms have important implications for the ongoing debates over comprehensive immigration reform in the US and elsewhere.
urn:nbn:de:101:1-20091105998
Keywords: F22; I2; J62; 330; Immigration; citizenship; redistributive policies; political economy; Einwanderung; Staatsangehörigkeit; Verteilungspolitik; Migrationspolitik; Sozialstaat; Public Choice; Theorie